PROBLEMATIKA FAKTOR-FAKTOR PRODUKSI DALAM ILMU EKONOMI MODERN: SEBUAH UPAYA AKADEMIK DALAM INTEGRASI DAN ISLAMISASI KONSEP PRODUKSI - Khoirul Umam; Alfiansyah Topandi Harahap (CENDEKIA: Jurnal Studi Keislaman, 2022)
This study aims to determine the factors in the production concept in the western view and how the solutions provided by Islam are through integration and islamization methods which are then constructed through an Islamic worldview. The research method uses qualitative research with library research. The results of this study indicate that the western production theory has a capitalist economic system with worldly principles with an understanding that overrides God, namely income, wealth and prosperity in the world. Therefore, Islamic economics comes with bringing the best solution to the production concept that is widely embraced by western society by causing various damage, then the Islamization of the western production concept is based on the Islamic Worldview as the basis and the center is aqidah being the best solution to straighten the concept. The actual production offers three factors of production of renewal, namely the Caliph fil ardh (Human), Nature and all its contents and devotion to God Almighty as its pillar. The three offers of Islamic production renewal factors provide guidance and direction for good production methods so as to create halal and thoyyibah production results in order to achieve the benefit and welfare of the people.